Lily Search for Sexual Identity in Malinda Lo's Last Night at the Telegraph Club - Prasetyo, Alifah Adjani; Pramesti, Tri (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This study explores the journey of sexual identity discovery in Malinda Lo’s novel Last Night at The Telegraph Club, focusing on the main character Lily, a Chinese American teenager in the 1950s. The writer of this study used qualitative and descriptive research methods to examines into Lily's experiences. By employing Vivienne Cass’s model of six stage of homosexual identity formation and applies queer theory as a means for doing queer criticism. However, in this study, only five stages are found in the main character's journey, as Lily does not reach the stage of pride due to external rejections and societal pressures. This study highlights the intersection of cultural expectations and sexual identity, illustrating the importance of supportive communities on self-acceptance. Lily’s story portrays the ongoing challenges faced by homosexual individuals in conservative societies, emphasizing the need for broader societal acceptance and change. Through this research, the study aims to contribute to the understanding of sexual identity development and the critical importance of supportive environments for homosexual individuals.